The Role of Bhabinkamtibmas as an Effort Prevention of Drug Abuse in the Jurisdiction of the Sidoarjo Police - Thami, Ahnaf; Kusuma, Alif Bryan Pradana; Mandica, Andi Gibran Gani (Akademi Kepolisian Republik Indonesia, 2025)
One of the areas that has a high tendency for drug distribution and abuse is Sidoarjo. Sidoarjo has the largest population after Surabaya, with a total population of 2,267,000. Therefore, the high use of narcotics in the Sidoarjo area is due to the large population. The Sidoarjo Police use preemptive efforts through counseling to overcome the problem of abuse of drugs in Regency Sidoarjo. Study This is included in the category of field research, which is conducted directly in the field to provide an objective picture of the reality of the problem being studied. This type of research seeks to interpret various aspects such as observed conditions or relationships, developing opinions, processes, consequences or effects, and emerging trends. This type of research will provide a detailed explanation of how Bhabinkamtibmas optimizes counseling in efforts to prevent drug abuse in the jurisdiction of the Police Sidoarjo. The constraint or obstacle found by member Public Order Officer Police Station Sidoarjo is the performance of Bhabinkamtibmas Polresta Sidoarjo is still inefficient and ineffective. Inefficient due to minimal organizational input and inability to produce high output, productivity is low, and individual performance is still lacking. While not practical, because from the objective approach, it is proven by the inequality between the implementation of counseling.